Exploration of Socio-Scientific Issues Learning Media for Science Literacy through Hypercontent E-Module - Widyastuti , Meyliana Puji; Safitri, Erna Retna; Desi, Desi (Papanda Publisher, 2025)
The low achievement of students' science literacy in Indonesia, as shown by the Programme for International Student Assessment (PISA), indicates a gap between students' mastery of concepts and their ability to apply them in real-life situations. One relevant approach to addressing this challenge is the provision of learning media based on socio-scientific issues in the form of interactive, multimodal, and hypercontent e-modules. This research aims to explore the needs of students and teachers as the basis for developing the e-module. The research subjects involved 71 students and two science teachers at SMP Negeri 11 Bayung Lencir. Data was collected through observations, interviews, and questionnaires. The observation results show that learning remains teacher-centered, lecture-dominant, and relies on a limited package of books, and is less related to daily life. Student interviews revealed that science learning tends to be monotonous; however, they show a strong tendency towards visual-based and group discussion-based learning. Direct practice, as well as digital media that are integrated with environmental, health, and technological issues. The teacher emphasized the need for innovative media that is contextual and digital-based. The questionnaire data reinforces this finding, where 74.6% of students are looking for additional materials outside of the package book, 54.9% need additional learning media, but only 9.8% have used e-modules. In addition, almost half of the students (49.2%) stated that they prefer digital-based learning and are interested in science materials related to socio-scientific issues. This finding confirms the urgency of developing hypercontent e-modules with socio-scientific issue-content as a pedagogical as well as technological solution to support the defense of science that is more meaningful, collaborative, and contributory to improving the science literacy of junior high school students.